Pengaruh Job Meaningfulness Terhadap Kinerja Tenaga Kesehatan Melalui Work Engagement (Studi: Puskesmas Mokoau) Kota Kendari Sulawesi Tenggara - Rahman (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2026)
The performance of health workers is an important element in ensuring the quality of primary health services. In addition to technical and structural factors, psychological aspects such as job meaningfulness and work engagement are increasingly recognized as playing a role in improving performance. Health workers who interpret their work as something of value tend to show higher work attachment, which ultimately has an impact on performance. This study aims to analyze the effect of job meaningfulness on the performance of health workers through work engagement at the Mokoau Health Center, Kendari City. This study used a quantitative approach with a cross-sectional design. All health workers at the Mokoau Health Center as many as 70 people were involved as respondents through the total sampling technique. Data were collected using a structured questionnaire and analyzed using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method using SmartPLS version 4.0. The results of the analysis showed that job meaningfulness had a positive and significant effect on work engagement (β = 0.563; p < 0.05). Furthermore, work engagement had a positive and significant effect on the performance of health workers (β = 0.638; p < 0.05). The indirect influence test proved that work engagement significantly mediated the influence between job meaningfulness and performance (β = 0.360; p < 0.05). Job meaningfulness improves the performance of health workers through strengthening work engagement. Therefore, the HR management strategy at the Health Center needs to be directed at strengthening the meaning of work and work attachment to improve performance in a sustainable manner.